An Analysis of the Acceptance of the Mal Pelayanan Publik (MPP) Application Using a Modified Technology Acceptance Model (TAM) - Pajrin, Gumilar Samsul; Bagye, Wire; Imtihan, Khairul (Jambura Journal of Electrical and Electronics Engineering, 2025)
This study was conducted to evaluate the extent to which users accept the use of the Public Service Mall (Mal Pelayanan Publik or MPP) application in Central Lombok Regency, employing a modified Technology Acceptance Model (TAM) approach. The modification involved the integration of additional constructs, namely trust, subjective norms, experience, and user experience, to provide a more comprehensive understanding of the factors influencing acceptance and the intention to continue using the MPP application. A quantitative approach was adopted, utilizing a survey method with questionnaires distributed online to MPP application users. Data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with the aid of SmartPLS version 4.0 software. Among the eleven hypotheses proposed in the model, only three were found to be statistically significant. The findings indicate that Perceived Usefulness (PU) positively influences Attitude Toward Using (ATU), which in turn positively affects Behavioral Intention to Use (BI), and subsequently, BI contributes positively to Continuance Intention (CI) in using the MPP application. These results highlight the critical role of perceived usefulness—or users' assessment of system functionality—as a primary determinant in shaping attitudes and usage intentions. Based on these findings, the study recommends enhancing digital literacy, developing application features that align with user needs, and strengthening the capabilities of digital service personnel to ensure sustainable utilization of technology in the public service sector.Penelitian ini dilakukan untuk mengevaluasi sejauh mana pengguna menerima penggunaan aplikasi Mal Pelayanan Publik (MPP) di Kabupaten Lombok Tengah dengan menggunakan pendekatan model Technology Acceptance Model (TAM) yang telah dimodifikasi. Modifikasi model mencakup tambahan konstruk trust, subjective norms, experience, dan user experience agar dapat menghasilkan pemahaman yang lebih lengkap pada aspek yang memengaruhi penerimaan dan niat keberlanjutan penggunaan aplikasi MPP. Pendekatan kuantitatif digunakan dengan metode survei melalui kuesioner yang disebarkan secara daring kepada pengguna aplikasi MPP.  Analisis data dilakukan menggunakan pendekatan Partial Least Squares Structural Equation Modeling (PLS-SEM) dengan bantuan perangkat lunak SmartPLS versi 4.0. Dari sebelas hipotesis yang diajukan dalam model, hanya tiga yang terbukti signifikan secara statistik. Temuan tersebut menunjukkan bahwa Perceived Usefulness (PU) memiliki pengaruh positif terhadap Attitude Toward Using (ATU), ATU secara positif memengaruhi Behavioral Intention to Use (BI), dan BI juga berkontribusi positif terhadap Continuance Intention (CI) dalam penggunaan aplikasi MPP. Temuan ini menekankan pentingnya persepsi kegunaan atau panandangan terhadap fungsionalitas sebagai penentu utama dalam membentuk sikap dan niat penggunaan aplikasi. Penelitian ini merekomendasikan peningkatan edukasi digital, pengembangan fitur yang relevan dengan kebutuhan pengguna, serta penguatan kapasitas SDM pelayanan digital untuk mendukung keberlanjutan pemanfaatan teknologi di sektor pelayanan publik.